Neodymium biosorption from acidic solutions in batch system - Palmieri, M. C.; Garcia, O.; Melnikov, P. (Elsevier B.V., 2000)
Biosorption of neodymium in batch experiments took similar to 2 h to achieve the equilibrium biosorbent-metal for all microorganisms tested. The best biosorption coefficient at a constant pH value of 1.5 was obtained using the microalgae Monoraphidium sp. (1521 mg g(-1) cell), followed by Bakers' yeast (313 mg g(-1) cell), Penicillium sp. (178 mg g(-1) cell), and activated carbon (61 mg g(-1) cell). When compared to the biosorption of other metals, these results pointed out to the application of biosorption in neodymium recovery from acidic solutions. (C) 2000 Elsevier B.V. Ltd. All rights reserved.
Keywords: biosorption; biorecovery; bioaccumulation; rare-earths; neodymium; lanthanides